The Effect of Chinese Demand and Supply Shocks on Peruvian Exporters. Issue 8 (2nd August 2016) - Rabanal, Jean Paul; Rabanal, Olga A.
ABSTRACT: We study the impact of Chinese supply and demand shocks on Peruvian firm-product exports. Our results indicate that Chinese competition has a positive and significant effect on Peruvian firm exports, which suggests that firms are either (1) concentrating on markets where competition is tougher, (2) increasing R&D efforts, and/or (3) benefiting from a comparative advantage. The demand from China also has an overall positive and significant effect on Peruvian exports, but negative effect on the subset of data pertaining to minerals. This suggests that Peruvian commodities are being redirected from other markets to China.